OPTIMALISASI PEMANFATAAN MEDIA SOSIAL SEBAGAI STRATEGI PROMOSI TERHADAP PENGEMBANGAN WISATA TAMAN NASIONAL MERU BETIRI, KABUPATEN JEMBER, DAN BANYUWANGI - Sahrian Samsi; Diajeng Putri Maesti; Asep Parantika (Nawasena: Jurnal Ilmiah Pariwisata, 2022)
Administratively, Meru Betiri National Park includes Banyuwangi Regency and Jember Regency, East Java. This research aims to optimize the use of social media for tourism development in Meru Betiri National Park. The research method used is a qualitative method with descriptive analysis to identify social media promotion strategies for the development of Meru Betiri National Park tourism. The technique for collecting data sources uses literature studies and other journal references. Meru Betiri National Park is mostly a tropical rainforest located in the Banyuwangi and Jember districts. The biodiversity in Meru Betiri National Park can be an object of attraction for tourists. Meru Betiri National Park conducts advertising promotions on the websites tribunnewswiki.com and katadata.co.id.